CONCEPT OF FEMICIDE AND FEMICIDE IN THE MEDIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
Every day we witness a new murder of a woman or girl both in the region and in the world. There are also cases of femicide in the Republic of North Macedonia. Violence against women and girls will never end. Women are the most frequent victims of violence and murder in the family and relationship. Femicide is the most extreme manifestation of abuse and violence by men against women. It occurs as a result of any type of gender-based violence, such as physical assault, rape, forced motherhood or genital mutilation. Femicide, as well as the consequences of its application in various research areas, have been explored from a historical, legal, international and activist point of view, so it is very important how femicide is conveyed through the media. The media play a very important role in prevention, the way in which the murder of a woman is transmitted plays a big role in the mentality of the population, which terms are used, etc. A sensationalist drama is often created from that crime drama, which abounds with ironic and primitive comments on the population, especially on the part of the male sex.Keywords: Femicide, woman, murder, violence, media, victim